TUPOKSI BADAN PERMUSYAWARATAN DI DESA KANTANAN - Serly SB Sihira (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2023)
The Village Consultative Body, hereinafter referred to as the BPD, is an institution which is the embodiment of democracy in supervising the administration of village governance as an element of the BPD's function of accommodating and channeling community aspirations. As the subject of development, of course, community members should be involved in determining development plans so that the development plans to be implemented can directly touch the needs of the community. However, despite having a very strategic position, many BPDs are still not optimal in carrying out their functions. The research objective is to determine the role and function of the BPD in Kantanan Village. The research method used is descriptive qualitative, the research location is in Kantanan Village. Data collection techniques were in the form of observation, interviews and documentation which were then analyzed using qualitative data based on Miles and Huberman's concepts. The results showed that the function of the Kantanan Village Consultative Body in supervising village regulations and the village spending income budget had been implemented properly, although the research results found obstacles such as lack of facilities and outreach, as well as technical guidelines that should have been provided by the Kantanan village government. The biggest inhibiting factors in the implementation of BPD supervision of the Kantanan Village Government are allowances from BPD members, facilities, and understanding of the duties and functions of the BPD in administering Village Government, as well as other factors, such as mental attitude, and existing customary/family factors.